2005
DOI: 10.1016/j.femsim.2005.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional genome of the human pathogenic fungusParacoccidioides brasiliensis

Abstract: Paracoccidioides brasiliensis is a dimorphic and thermo-regulated fungus which is the causative agent of paracoccidioidomycosis, an endemic disease widespread in Latin America. Pathogenicity is assumed to be a consequence of the cellular differentiation process that this fungus undergoes from mycelium to yeast cells during human infection. In an effort to elucidate the molecular mechanisms involved in this process a network of Brazilian laboratories carried out a transcriptome project for both cell types. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 91 publications
0
15
0
4
Order By: Relevance
“…The presence of a Paracoccidioides mating type locus, MAT1-1, which is a homologue of that in Aspergillus nidulans and other components of the pheromone response pathway, was previously reported from transcriptomic analyses of both morphological phases of P. lutzii strain Pb01 (17,18). Torres et al (19) identified the presence and expression of MAT1-1 and MAT1-2 in the P. brasiliensis phylogenetic species complex, suggesting a sexual cycle in this fungus.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The presence of a Paracoccidioides mating type locus, MAT1-1, which is a homologue of that in Aspergillus nidulans and other components of the pheromone response pathway, was previously reported from transcriptomic analyses of both morphological phases of P. lutzii strain Pb01 (17,18). Torres et al (19) identified the presence and expression of MAT1-1 and MAT1-2 in the P. brasiliensis phylogenetic species complex, suggesting a sexual cycle in this fungus.…”
mentioning
confidence: 70%
“…The MAT1-1 transcript of P. lutzii strain Pb01 was identified during the EST sequencing project (17,39). Recently, the chromosomal structures of the MAT1-1 and MAT1-2 loci of P. brasiliensis Pb3 and Pb18 and P. lutzii Pb01 were identified based on comparative genomic analyses with other dimorphic fungal pathogens and dermatophytes (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, es poco lo que se conoce sobre el proceso de germinación de conidia a micelio. Restrepo et al (16) Con respecto a la evaluación de los mecanismos moleculares y de la expresión de genes en los diferentes estadios morfológicos, se han realizado varios estudios utilizando estrategias, tales como la construcción de librerías EST (Expressed Sequence Tag) y los microarreglos, con los que se ha logrado recopilar un gran número de genes que se expresan durante los estadios de micelio y levadura (5,17,18), así como genes que presentan expresión diferencial durante la transición de micelio a levadura (6,19). Estos estudios han abierto las puertas al conocimiento de los mecanismos genéticos que rigen la diferenciación morfológica de P. brasiliensis; sin embargo, los procesos moleculares involucrados en los cambios morfológicos de las conidias y los genes involucrados en su transición a levadura y germinación a micelio, han sido muy poco estudiados.…”
Section: Identification Of Genes Associated With Germination Of Conidunclassified
“…A mudança de fase "fungo filamentoso-levedura" também colabora na expressão dos genes de virulência e na evasão da resposta do hospedeiro 5 . A fisiologia fúngica também interfere com a expressão da doença, onde a maior ocorrência de paracoccidioidomicose em homens e trabalhadores rurais possivelmente reflete a maior exposição desses aos propágulos do fungo 8 , bem como o efeito que os hormônios femininos, em particular β-estradiol, têm na fisiologia fúngica, inibindo a transição da fase micelial para o estado leveduriforme, nos pulmões, prevenindo o desenvolvimento da infecção 19,20,21 . A despeito do conhecimento disponível sobre esse gênero microbiano, o nicho ecológico por ele ocupado no solo, nas diferentes comunidades microbianas, ainda necessita de elucidação 4 .…”
Section: Introductionunclassified